What makes a music track popular in online social networks? - REN, Jing (Institutional Knowledge at Singapore Management University, 2016)
Tens of thousands of music tracks are uploaded to the Internet every day through social networks that focus on music and videos, as well as portal websites. While some of the content has been popular for decades, some tracks that have just been released have been completely ignored. So what makes a music track popular? Can we predict the popularity of a music track before it is released? In this research, we will focus on an online music social network, Last.fm, and investigate three key factors of a music track that may have impact on its popularity. They include: the music content, the artist reputation and the social context of the music. The results suggest that we can predict the future popularity of music with around 80% accuracy using just these three factors. We also found out that in the social networks scenario, the content of the music seems to be an surprisingly important factor that determines the popularity of a track online.